A method for modifying ion membranes for selective separation of nitrate ions

By interfacial polymerization on the anion exchange membrane, a hydrophobic polymer coating is formed, which solves the problem of insufficient separation efficiency between the same ions of the traditional electrodialysis method, and efficient selective separation of nitrate ions is achieved, thereby reducing nitrate pollution in groundwater.

CN119158424BActive Publication Date: 2025-04-15RES CENT FOR ECO ENVIRONMENTAL SCI THE CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411598581.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-15
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The separation efficiency of traditional electrodialysis methods between homovalent ions (nitrate ions and chloride ions) is insufficient, making it difficult to effectively remove nitrate pollution in groundwater.

Method used

By performing interfacial polymerization on an anion exchange membrane, an anionic adhesive and polymerized cationic monomer compounds are used to form a hydrophobic polymer coating, which enhances nitrate ion selectivity of the membrane.

Benefits of technology

The selective permeability and migration rate of nitrate ions are significantly improved, the target selective separation of nitrate ions is achieved, and nitrate pollution in groundwater is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158424B_ABST
    Figure CN119158424B_ABST
Patent Text Reader

Abstract

The present invention relates to an ion membrane modification method for selectively separating nitrate ions. The surface of a base ion membrane is modified by coating with a hydrophobic polymer using an interfacial polymerization method. The surface of the base ion membrane is coated with a hydrophobic polymer coating to improve the selective permeability and migration rate of nitrate ions on the base ion membrane. First, the base ion membrane is activated and cleaned, and then the base ion membrane is placed in a hydrophobic polymer solution for treatment. Finally, the modified base ion membrane is cleaned and post-processed. The modified base ion membrane prepared by the present invention has high separation selectivity and good stability when used for desalination treatment in an electrodialysis device, and can selectively separate nitrate ions, achieving a selectivity of nitrate ions greater than that of chloride ions, and the modification operation is simple and easy, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation, and in particular relates to an ion membrane modification method for selectively separating nitrate ions. Background Art

[0002] With the accelerated advancement of industrialization and agricultural modernization, unreasonable production activities have made the water environment face increasingly severe pollution challenges. At the same time, due to the increase in nitrogen fertilizer application, the change in land use patterns and the increase in the recycling rate of domestic wastewater, the degree of nitrate pollution in groundwater has gradually increased, which has become an environmental problem that needs to be solved urgently worldwide. As an efficient and environmentally friendly membrane separation method, electrodialysis technology has always shown broad application prospects in the fields of water pollution control and resource recovery. However, with the continuous development of electrodialysis technology and the growing demand for it in the industry, the traditional electrodialysis method has gradually revealed its inadequacy in the separation efficiency between ions of the same value (nitrate ions and chloride ions). Therefore, more and more research is focused on exploring anion exchange membranes suitable for the selective separation of ions of the same value (nitrate ions and chloride ions).

[0003] Ion selectivity is a membrane property that mainly works at the membrane-solution interface. Therefore, surface modification of ion exchange membranes is an effective method for regulating membrane ion selectivity, which mainly includes solution casting, electrodeposition, layer-by-layer assembly, and interfacial polymerization. Among them, the membrane modified based on interfacial polymerization has little effect on or slightly improves the flux of monovalent anions while achieving higher monovalent anion selectivity, which can effectively solve the "trade-off" effect between ion flux and selectivity. Therefore, in order to enhance the performance of nitrate ion selectivity, the present technical invention applies organic monomers to anion exchange membranes for interfacial polymerization, and the prepared modified membranes make full use of the advantages of organic polymers and the unique physical and chemical characteristics of nitrate ions, thereby improving the nitrate ion selectivity of the membrane. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an ion membrane modification method for selectively separating nitrate ions. The membrane can be used in the electrodialysis desalination process to selectively separate nitrate ions and reduce nitrate pollution in groundwater. The treated groundwater can be used as drinking water or high-quality industrial water. The entire industry provides an effective ion membrane modification method for selectively separating nitrate ions to achieve a selectivity of nitrate ions greater than that of chloride ions.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0006] An ion membrane modification method for selectively separating nitrate ions, comprising:

[0007] The anionic adhesive is applied to the base ion membrane to form an anionic adhesive layer, and then in a reaction solution containing a polymerized cationic monomer compound, an interfacial polymer layer is formed by interfacial polymerization, and then the preparation of the anionic adhesive layer and the interfacial polymer layer is repeated 0 to 4 times to obtain a modified anion exchange membrane;

[0008] The anionic binder is selected from anionic polyurethanes having diethylene glycol groups, 2-nitro groups and 1,3-dihydroxyacetone diether groups.

[0009] Preferably, the polymeric cationic monomer compound is one of piperidine, pyrrole, dimethyldiallyl ammonium chloride, imidazole, chitosan and aryl piperidine aryl nitrogen heterocycle; or, the polymeric cationic monomer compound is a mixture of two monomer substances among piperidine, pyrrole, dimethyldiallyl ammonium chloride, imidazole, chitosan and aryl piperidine aryl nitrogen heterocycle.

[0010] Preferably, the reaction solution is formed by adding a polymerized cationic monomer compound into a reaction base solution, the reaction base solution is a ferric chloride solution, and the concentration of ferric chloride in the reaction base solution is 0.1-1 mol / L.

[0011] Preferably, the anionic binding layer is activated by NaOH solution.

[0012] Preferably, the substrate ion membrane is an anion exchange membrane, and the anion exchange membrane is selected from a homogeneous anion exchange membrane, a semi-homogeneous anion exchange membrane, and a heterogeneous anion exchange membrane.

[0013] Preferably, the mass ratio of the base ion membrane to the anionic binder is 95:5-25.

[0014] Preferably, the anion binding layer and the interface polymer layer form a hydrophobic polymer coating, and the number of layers of the hydrophobic polymer coating in the modified ion exchange membrane is 1 to 5 layers.

[0015] Preferably, the preparation of anionic polyurethane comprises:

[0016] S1: Phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate and a hydroxy compound are mixed and reacted to generate an intermediate 1; the hydroxy compound is at least one of 2-nitropropylene glycol and 1,3-dihydroxyacetone diether; wherein, when 2-nitropropylene glycol and 1,3-dihydroxyacetone diether are involved in the preparation of anionic polyurethane, the prepared anionic polyurethane is used for the modification of anion exchange membranes and electrodialysis desalination, which can effectively improve the selectivity of nitrate ions, which is mainly attributed to the use of 2-nitropropylene glycol and 1,3-dihydroxyacetone diether to introduce a new structure into the anionic polyurethane. The prepared anionic polyurethane is used for the preparation of modified anion exchange membranes, which can effectively regulate the surface structure of the modified anion exchange membranes, thereby effectively improving the selectivity of the modified anion exchange membranes for nitrate ions.

[0017] S2: Continue to raise the temperature of intermediate 1, keep the temperature to react, add acetone, and obtain intermediate 2;

[0018] S3: Adjust the pH of the intermediate 2, then add deionized water for emulsification, and remove the acetone in vacuo to obtain the anionic polyurethane as claimed in claim 3.

[0019] Preferably, the modified anion exchange membrane prepared by the ion membrane modification method is used for selective separation of nitrate ions.

[0020] Preferably, the modified anion exchange membrane is used in wastewater treatment and / or sewage purification.

[0021] The invention provides an ion membrane modification method for selectively separating nitrate ions. The surface of the ion membrane is modified by coating with a hydrophobic polymer by an interfacial polymerization method. The surface of the ion membrane is coated with a hydrophobic polymer coating, thereby improving the selective permeability and migration rate of nitrate ions on the ion membrane.

[0022] Preferably, in an ion membrane modification method for selectively separating nitrate ions, the surface of the ion membrane is coated with a hydrophobic polymer coating.

[0023] Preferably, in a method for modifying an ion membrane for selectively separating nitrate ions, the hydrophobic water contact angle of the hydrophobic polymer coating is greater than 90°; or, the hydrophobic water contact angle of the hydrophobic polymer coating is greater than 100°; or, the hydrophobic water contact angle of the hydrophobic polymer coating is 120°;

[0024] Preferably, in an ion membrane modification method for selectively separating nitrate ions, the thickness of the hydrophobic polymer coating is 0.01 to 10 μm.

[0025] Preferably, in an ion membrane modification method for selectively separating nitrate ions, the molecular weight of the hydrophobic polymer coating is 4000-220000 g / mol, or the molecular weight of the hydrophobic polymer coating is 100000-160000 g / mol.

[0026] More preferably, in an ion membrane modification method for selectively separating nitrate ions, the mass ratio of the base ion membrane to the anionic binder is 95:5-25.

[0027] Preferably, in an ion membrane modification method for selectively separating nitrate ions, the prepared modified anion exchange membrane is used for selectively separating ions in an electrodialysis device, and is particularly suitable for selectively separating ions in a multi-ion system.

[0028] More preferably, in an ion membrane modification method for selectively separating nitrate ions, the ions to be selectively separated in a multi-ion system are nitrate ions, and the ions in the multi-ion system include chloride ions, sulfate ions and nitrate ions.

[0029] More preferably, in an ion membrane modification method for selectively separating nitrate ions, the modified anion exchange membrane is used in an electrodialysis process to achieve greater selectivity for nitrate ions than for chloride ions.

[0030] Preferably, a method for preparing a modified anion exchange membrane comprises:

[0031] S1: coating an anionic adhesive on a base ion membrane, activating the base ion membrane with a NaOH solution, and then immersing the base ion membrane in a reaction base liquid, adding a polymerized cationic monomer compound into the reaction base liquid, stirring, and promoting an interfacial polymerization reaction to obtain an intermediate 1;

[0032] S2: coating the surface of the intermediate 1 with an anionic adhesive again, and then immersing the intermediate 1 in the reaction base liquid for interfacial polymerization, and repeating the above polymerization reaction process to obtain the intermediate 2;

[0033] S3: drying the intermediate 2, cleaning the surface impurities after drying, and drying again to obtain a modified ion exchange membrane.

[0034] Preferably, the anionic binder is anionic polyurethane.

[0035] Preferably, the substrate ion membrane is an anion exchange membrane, and the anion exchange membrane is selected from a homogeneous anion exchange membrane, a semi-homogeneous anion exchange membrane, and a heterogeneous anion exchange membrane.

[0036] More preferably, the anion exchange membrane can be any commercial or homemade anion exchange membrane. Commercial anion exchange membranes include but are not limited to anion exchange membranes produced by Lanran, Yiwei Hydrogen Energy, and Jinqiu.

[0037] More preferably, the mass ratio of the base ion membrane to the anionic binder in S1 is 95:5-25.

[0038] Preferably, the concentration of the NaOH solution is 0.05-0.2 mol / L.

[0039] Preferably, the activation time is 5 to 30 min.

[0040] Preferably, the reaction base liquid is a ferric chloride solution with a concentration of 0.1-1 mol / L.

[0041] Preferably, the polymeric cationic monomer compound is one of piperidine, pyrrole, dimethyldiallylammonium chloride, imidazole, chitosan and arylpiperidine aryl nitrogen heterocycle; or a mixture of two monomer substances.

[0042] More preferably, the two monomer substances are mixed, wherein the mass ratio of the two monomer substances is 1:9 to 9:1.

[0043] More preferably, the volume ratio of pyrrole to ferric chloride solution is 0.5-10%.

[0044] Preferably, the stirring speed is 50-400 r / min.

[0045] Preferably, the number of repetitions is 1 to 4.

[0046] Preferably, the layer structure of the modified ion exchange membrane is 2 to 5 layers.

[0047] Preferably, the temperature of the system for cleaning surface impurities is 10-50°C.

[0048] Preferably, the solution used for cleaning surface impurities includes an aqueous solution or an aqueous hydrochloric acid solution.

[0049] More preferably, the concentration of the aqueous hydrochloric acid solution is 0.1 to 1.5 mol / L.

[0050] Preferably, the drying temperature is 40-120°C and the drying time is 12-48 hours.

[0051] More preferably, a method for preparing anionic polyurethane is specifically:

[0052] S1: In a dry nitrogen atmosphere, phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate and hydroxyl compound are mixed and reacted, and the -NCO content of the system is detected. When the -NCO content reaches 35-50%, the temperature is increased, and a DMF solution of dimethylol propionic acid is added dropwise to react to generate intermediate 1;

[0053] S2: Continue to raise the temperature of intermediate 1 and keep the temperature to react. When the -NCO content reaches 20-33%, add acetone to obtain intermediate 2.

[0054] S3: After cooling the intermediate 2, a potassium hydroxide aqueous solution is added to adjust the pH, and then stirred and deionized water is added for emulsification. The acetone is removed under vacuum to obtain anionic polyurethane.

[0055] Preferably, the amount of phthalic anhydride polyester polyol used is 40 to 80 parts by weight.

[0056] Preferably, the amount of diethylene glycol is 4 to 8 parts by weight.

[0057] Preferably, the amount of toluene diisocyanate used is 10 to 50 parts by weight.

[0058] Preferably, in a method for preparing anionic polyurethane, the hydroxy compound is at least one of 2-nitroglycerine, 1,3-dihydroxyacetone diether and DL-glyceryl ether dimer. When DL-glyceryl ether dimer participates in the preparation of anionic polyurethane, the prepared anionic polyurethane is used for modification of anion exchange membrane and electrodialysis desalination, which can further improve the selectivity of nitrate ions. Since DL-glyceryl ether dimer contains dihydroxy groups, it can react with -NCO of toluene diisocyanate to form a new structure in the anionic polyurethane. The prepared anionic polyurethane is used for the preparation of modified anion exchange membrane, which can further effectively regulate the surface structure and chemical composition of the modified anion exchange membrane, thereby further effectively improving the selectivity of the modified anion exchange membrane for nitrate ions.

[0059] Preferably, the hydroxy compound is 2-nitroglycerin.

[0060] Preferably, the hydroxy compound is 2-nitroglycerin and 1,3-dihydroxyacetone diether.

[0061] Preferably, the hydroxy compound is 2-nitroglycerin, 1,3-dihydroxyacetone diether and DL-glycerol ether dimer.

[0062] Preferably, the amount of 2-nitropropylene glycol is 5 to 15 parts by weight.

[0063] Preferably, the amount of 1,3-dihydroxyacetone diether is 5 to 15 parts by weight.

[0064] Preferably, the amount of DL-glyceryl ether dimer is 2 to 12 parts by weight.

[0065] Preferably, the reaction temperature is 55-70° C. and the reaction time is 1.5-2.5 h.

[0066] Preferably, the temperature in S1 is raised to 65-75°C.

[0067] Preferably, the mass percentage of dimethylol propionic acid in the DMF solution is 5-6%, and the amount of the DMF solution of dimethylol propionic acid is 1-3 parts by volume. Among them, the amount of phthalic anhydride polyester polyol and the DMF solution of dimethylol propionic acid is 40-80g:1-3ml.

[0068] Preferably, the temperature in S2 is raised to 80-84° C., and the reaction time is kept at this temperature for 1-2 h.

[0069] Preferably, the amount of acetone is 40 to 60 parts by volume.

[0070] Preferably, the temperature is cooled to 28-35°C.

[0071] Preferably, the amount of the potassium hydroxide aqueous solution is 1 to 3 parts by volume.

[0072] Preferably, the stirring rate is 800-1200 r / min.

[0073] Preferably, the amount of deionized water used is 80 to 120 parts by volume.

[0074] Preferably, the vacuum degree is 2~8Pa.

[0075] The present invention is simple and easy to implement due to the interfacial polymerization process adopted. It only needs to place the anion exchange membrane coated with an anionic adhesive and the polymerized cationic monomer compound in a reaction bottom liquid, stir and polymerize, and then obtain the hydrophobic polymerization-modified anion exchange membrane after drying and washing. The product process quality is easy to control, which is conducive to industrial production, and can effectively improve the permselectivity and migration rate of nitrate ions on the ion membrane. Therefore, the present invention is an ion membrane modification method for selectively separating nitrate ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 This is a SEM schematic diagram of the surface and cross-section of the modified anion exchange membrane of Example 6.

[0077] Figure 2 Schematic diagram of the contact angle of anion exchange membrane before and after modification.

[0078] Figure 3 NO3 before and after modification - / Cl - Schematic diagram of the change of selectivity coefficient.

[0079] Figure 4 NO3 before and after modification - / SO4 2- Schematic diagram of the change of selectivity coefficient. DETAILED DESCRIPTION

[0080] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0082] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0083] Embodiment 1:

[0084] The invention discloses a method for preparing anionic polyurethane.

[0085] In a dry nitrogen atmosphere, phthalic anhydride polyester polyol, diethylene glycol and toluene diisocyanate are mixed and added into a four-necked flask equipped with a stirrer, a thermometer and a condenser for reaction, and the -NCO content of the system is detected. When the -NCO content reaches 40%, the temperature is raised for the first time, and a DMF solution of dimethylol propionic acid is added dropwise, and the temperature is raised for the second time, and the reaction is kept warm. When the -NCO content reaches 30%, acetone is added to obtain a carboxyl-terminated polyurethane prepolymer. After cooling, potassium hydroxide aqueous solution is added to adjust the pH, and then stirring and deionized water are added for emulsification. The acetone is removed under vacuum conditions to obtain anionic polyurethane. The dosage of phthalic anhydride polyester polyol is 60g, the dosage of diethylene glycol is 6g, the dosage of toluene diisocyanate is 30g, the reaction temperature is 65℃, the reaction time is 2h, the first temperature is raised to 70℃, the mass percentage of dimethylolpropionic acid in the DMF solution of dimethylolpropionic acid is 5.5%, the dosage of the DMF solution of dimethylolpropionic acid is 2ml, the second temperature is raised to 82℃, the insulation reaction time is 1.5h, the dosage of acetone is 50ml, cooled to 30℃, pH is 7.0, the stirring rate is 1000r / min, the dosage of deionized water is 100ml, and the vacuum degree is 5Pa.

[0086] Embodiment 2:

[0087] The invention discloses a method for preparing anionic polyurethane.

[0088] The difference between this embodiment and embodiment 1 is that 2-nitroglycerin and 1,3-dihydroxyacetone diether are added during the preparation of the anionic polyurethane, specifically:

[0089] In a dry nitrogen atmosphere, phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate, 2-nitropropylene glycol and 1,3-dihydroxyacetone diether are mixed and added into a four-necked flask equipped with a stirrer, a thermometer and a condenser for reaction, and the -NCO content of the system is detected. When the -NCO content reaches 40%, the temperature is raised for the first time, and a DMF solution of dimethylol propionic acid is added dropwise. The temperature is raised for the second time and the reaction is kept warm. When the -NCO content reaches 30%, acetone is added to obtain a carboxyl-terminated polyurethane prepolymer. After cooling, a potassium hydroxide aqueous solution is added to adjust the pH, and then stirring and deionized water are added for emulsification. The acetone is removed under vacuum conditions to obtain anionic polyurethane. The dosage of phthalic anhydride polyester polyol is 60g, the dosage of diethylene glycol is 6g, the dosage of toluene diisocyanate is 30g, the dosage of 2-nitroglycerin is 5g, the dosage of 1,3-dihydroxyacetone diether is 5g, the reaction temperature is 65°C, the reaction time is 2h, the first temperature is raised to 70°C, the mass percentage of dimethylolpropionic acid in the DMF solution of dimethylolpropionic acid is 5.5%, the dosage of the DMF solution of dimethylolpropionic acid is 2ml, the second temperature is raised to 82°C, the insulation reaction time is 1.5h, the dosage of acetone is 50ml, cooled to 30°C, the pH is 7.0, the stirring rate is 1000r / min, the dosage of deionized water is 100ml, and the vacuum degree is 5Pa.

[0090] Embodiment 3:

[0091] The invention discloses a method for preparing anionic polyurethane.

[0092] The difference between this embodiment and embodiment 2 is that 2-nitropropylene glycol and 1,3-dihydroxyacetone diether are added during the preparation of the anionic polyurethane, and the amount of 2-nitropropylene glycol and 1,3-dihydroxyacetone diether is 10 g. Apart from this, other conditions are the same as those in embodiment 2.

[0093] Embodiment 4:

[0094] The invention discloses a method for preparing anionic polyurethane.

[0095] The difference between this embodiment and embodiment 3 is that DL-glyceryl ether dimer is added during the preparation of anionic polyurethane, specifically:

[0096] In a dry nitrogen atmosphere, phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate, 2-nitropropylene glycol, 1,3-dihydroxyacetone diether and DL-glycerol ether dimer are mixed and added into a four-necked flask equipped with a stirrer, a thermometer and a condenser for reaction, and the -NCO content of the system is detected. When the -NCO content reaches 40%, the temperature is raised for the first time, and a DMF solution of dimethylol propionic acid is added dropwise. The temperature is raised for the second time and the reaction is kept warm. When the -NCO content reaches 30%, acetone is added to obtain a carboxyl-terminated polyurethane prepolymer. After cooling, a potassium hydroxide aqueous solution is added to adjust the pH, and then stirring and deionized water are added for emulsification. The acetone is removed under vacuum conditions to obtain anionic polyurethane. The amount of phthalic anhydride polyester polyol is 60g, the amount of diethylene glycol is 6g, the amount of toluene diisocyanate is 30g, the amount of 2-nitroglycerin is 10g, the amount of 1,3-dihydroxyacetone diether is 10g, the amount of DL-glyceryl ether dimer is 5g, the reaction temperature is 65°C, the reaction time is 2h, the first temperature is raised to 70°C, the mass percentage of dimethylolpropionic acid in the DMF solution of dimethylolpropionic acid is 5.5%, the amount of dimethylolpropionic acid DMF solution is 2ml, the second temperature is raised to 82°C, the insulation reaction time is 1.5h, the amount of acetone is 50ml, cooled to 30°C, the pH is 7.0, the stirring rate is 1000r / min, the amount of deionized water is 100ml, and the vacuum degree is 5Pa.

[0097] Embodiment 5:

[0098] The invention discloses a method for preparing anionic polyurethane.

[0099] The difference between this embodiment and embodiment 4 is that DL-glyceryl ether dimer is added during the preparation of the anionic polyurethane, and the amount of DL-glyceryl ether dimer used is 10 g. Apart from this, other conditions are the same as those in embodiment 4.

[0100] Comparative Example 1:

[0101] The invention discloses a method for preparing anionic polyurethane.

[0102] The difference between this embodiment and embodiment 1 is that 2-nitropropylene glycol is added during the preparation of the anionic polyurethane, specifically:

[0103] In a dry nitrogen atmosphere, phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate and 2-nitropropylene glycol are mixed and added into a four-necked flask equipped with a stirrer, a thermometer and a condenser for reaction, and the -NCO content of the system is detected. When the -NCO content reaches 40%, the temperature is raised for the first time, and a DMF solution of dimethylol propionic acid is added dropwise. The temperature is raised for the second time and the reaction is kept warm. When the -NCO content reaches 30%, acetone is added to obtain a carboxyl-terminated polyurethane prepolymer. After cooling, an aqueous potassium hydroxide solution is added to adjust the pH, and then stirring and deionized water are added for emulsification. The acetone is removed under vacuum conditions to obtain anionic polyurethane. The dosage of phthalic anhydride polyester polyol is 60g, the dosage of diethylene glycol is 6g, the dosage of toluene diisocyanate is 30g, the dosage of 2-nitroglycerin is 5g, the reaction temperature is 65°C, the reaction time is 2h, the first temperature is raised to 70°C, the mass percentage of dimethylolpropionic acid in the DMF solution of dimethylolpropionic acid is 5.5%, the dosage of the DMF solution of dimethylolpropionic acid is 2ml, the second temperature is raised to 82°C, the insulation reaction time is 1.5h, the dosage of acetone is 50ml, cooled to 30°C, the pH is 7.0, the stirring rate is 1000r / min, the dosage of deionized water is 100ml, and the vacuum degree is 5Pa.

[0104] Comparative Example 2:

[0105] The invention discloses a method for preparing anionic polyurethane.

[0106] The difference between this embodiment and embodiment 1 is that 1,3-dihydroxyacetone diether is added during the preparation of the anionic polyurethane, specifically:

[0107] In a dry nitrogen atmosphere, phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate and 1,3-dihydroxyacetone diether are mixed and added into a four-necked flask equipped with a stirrer, a thermometer and a condenser for reaction, and the -NCO content of the system is detected. When the -NCO content reaches 40%, the temperature is raised for the first time, and a DMF solution of dimethylol propionic acid is added dropwise. The temperature is raised for the second time and the reaction is kept warm. When the -NCO content reaches 30%, acetone is added to obtain a carboxyl-terminated polyurethane prepolymer. After cooling, a potassium hydroxide aqueous solution is added to adjust the pH, and then stirring and deionized water are added for emulsification. The acetone is removed under vacuum conditions to obtain anionic polyurethane. The dosage of phthalic anhydride polyester polyol is 60g, the dosage of diethylene glycol is 6g, the dosage of toluene diisocyanate is 30g, the dosage of 1,3-dihydroxyacetone diether is 5g, the reaction temperature is 65°C, the reaction time is 2h, the first temperature is raised to 70°C, the mass percentage of dimethylolpropionic acid in the DMF solution of dimethylolpropionic acid is 5.5%, the dosage of the DMF solution of dimethylolpropionic acid is 2ml, the second temperature is raised to 82°C, the insulation reaction time is 1.5h, the dosage of acetone is 50ml, cooled to 30°C, the pH is 7.0, the stirring rate is 1000r / min, the dosage of deionized water is 100ml, and the vacuum degree is 5Pa.

[0108] Embodiment 6:

[0109] This example uses the anionic polyurethane prepared in Example 1.

[0110] Anionic polyurethane was coated on homogeneous anion exchange membrane, activated by NaOH solution, immersed in ferric chloride solution, pyrrole was added to the ferric chloride solution, stirred by polytetrafluoroethylene stirring device to promote interfacial polymerization reaction; then the anion exchange membrane was placed in an oven to dry; and the surface impurities were cleaned with hydrochloric acid solution and dried to obtain a modified ion exchange membrane. The mass ratio of anionic polyurethane to anion exchange membrane was 5% / 95%, the concentration of NaOH solution was 0.1 mol / L, the activation time was 15 min, the concentration of ferric chloride solution was 0.6 mol / L, the volume ratio of pyrrole to ferric chloride solution was 0.5%, the stirring speed was 150 r / min, the drying temperature was 90 ℃, the drying time was 36 h, the temperature for cleaning was 40 ℃, the concentration of hydrochloric acid solution was 0.5 mol / L, the drying temperature was 90 ℃, and the drying time was 12 h.

[0111] The reaction process of interfacial polymerization is as follows:

[0112] .

[0113] For the structural characterization of anion exchange membranes, field emission scanning electron microscopy (SEM) can be used to analyze the surface morphology and cross-sectional morphology of modified ion exchange membranes, obtain the coating of polymers on the surface of anion exchange membranes, and then evaluate the uniformity of polymer coating. Figure 1 shown. Figure 1 (a) is the SEM of the unmodified anion exchange membrane. The surface of the unmodified anion exchange membrane is uniform and smooth. Figure 1 (b) is the SEM of the anion exchange membrane after modification by in-situ polymerization of pyrrole. The roughness of the surface of the anion exchange membrane increases significantly after modification. Figure 1 (c) is the SEM of the modified anion exchange membrane under a 10 μm electron microscope. At this time, it can be clearly observed that the surface of the modified anion exchange membrane presents a cluster structure, which is consistent with the electron microscope microscopic morphology of polypyrrole. Figure 1 (d) is the SEM of the cross-section of the modified anion exchange membrane. It can be seen that a layer of polypyrrole is attached to the surface of the modified anion exchange membrane, which further verifies the successful preparation of the modified anion exchange membrane.

[0114] The static water contact angle of the anion exchange membrane surface was tested by contact angle to characterize the hydrophilicity and hydrophobicity of different types of anion exchange membranes. The water contact angle of the unmodified anion exchange membrane was 71.93°, and the water contact angle of the modified anion exchange membrane was 98.35°. Compared with the unmodified anion exchange membrane, the hydrophobicity of the modified anion exchange membrane surface was enhanced.

[0115] The anion exchange membrane is applied to a small electrodialysis device, the dilute chamber is a 0.1 mol / L mixed solution of NaCl, Na2SO4, and NaNO3, and the concentrated chamber is a 0.01 mol / L mixed solution of NaCl, Na2SO4, and NaNO3. After operation, the selectivity coefficient is calculated as follows:

[0116]

[0117]

[0118] Where J is the anion flux; V is the volume of the circulating solution in the concentration chamber; C0 is the concentration of anions in the concentration chamber when the electrodialysis time is 0; C t is the concentration of anions in the concentration chamber when the electrodialysis time is t; A m is the effective area of ​​the anion exchange membrane; J A - for A - Flux, J B - for B - Flux; C A- and C B- A- , B - The molar concentration of A - Represents NO3 - , B - Represents Cl - or SO4 2- ; is the selectivity coefficient, When it is greater than 1, it means NO3 - The selectivity is greater than that of Cl - or SO4 2- The selectivity, When it is less than 1, it means NO3 - The selectivity is less than Cl - or SO4 2- selectivity.

[0119] NO3 of unmodified anion exchange membrane - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 1.2 and 1.5, respectively, indicating that the modification can effectively improve the selectivity of nitrate ions.

[0120] Embodiment 7:

[0121] This example uses the anionic polyurethane prepared in Example 1.

[0122] Anionic polyurethane was coated on a heterogeneous anion exchange membrane, and the anion exchange membrane was activated by a NaOH solution, and then immersed in a ferric chloride solution, pyrrole was added to the ferric chloride solution, and a polytetrafluoroethylene stirring device was used to stir the solution to promote the interfacial polymerization reaction, thereby obtaining an intermediate 1. The mass ratio of anionic polyurethane to anion exchange membrane was 5% / 95%, the concentration of NaOH solution was 0.1 mol / L, the activation time was 15 min, the concentration of ferric chloride solution was 0.6 mol / L, the volume ratio of pyrrole to ferric chloride solution was 2%, and the stirring speed was 150 r / min.

[0123] Anionic polyurethane was coated again on the prepared intermediate 1, and then immersed in ferric chloride solution for interfacial polymerization reaction, and the above polymerization reaction process was repeated to obtain intermediate 2; then intermediate 2 was placed in an oven for drying, and surface impurities were cleaned with hydrochloric acid solution, and dried to obtain a modified ion exchange membrane. The mass ratio of anionic polyurethane to anion exchange membrane was 5% / 95%, the concentration of NaOH solution was 0.1 mol / L, the activation time was 15 min, the concentration of ferric chloride solution was 0.6 mol / L, the volume ratio of pyrrole to ferric chloride solution was 2%, the stirring speed was 150 r / min, the number of repetitions was 2, the modified ion exchange membrane was a 3-layer structure, the drying temperature was 90 ℃, the drying time was 36 h, the temperature for cleaning surface impurities was 40 ℃, the concentration of hydrochloric acid solution was 0.5 mol / L, the secondary drying temperature was 90 ℃, and the secondary drying time was 12 h.

[0124] The water contact angle of the modified anion exchange membrane is 109.09°. Compared with the unmodified anion exchange membrane, the hydrophobicity of the surface of the modified anion exchange membrane is enhanced.

[0125] The anion exchange membrane was applied to a small electrodialysis device under the same conditions as in Example 6. - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 1.9 and 6.4, respectively, indicating that the modification can effectively improve the selectivity of nitrate ions.

[0126] Embodiment 8:

[0127] This example uses the anionic polyurethane prepared in Example 2. Other conditions are the same as those in Example 7.

[0128] The anion exchange membrane prepared in this example was applied to a small electrodialysis device under the same conditions as in Example 7. - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2-The selectivity coefficients are 2.5 and 7.0, respectively, indicating that the selectivity of nitrate ions is effectively improved.

[0129] Embodiment 9:

[0130] This example uses the anionic polyurethane prepared in Example 3, except that other conditions are the same as those in Example 7.

[0131] The anion exchange membrane prepared in this example was applied to a small electrodialysis device under the same conditions as in Example 7. - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 3.1 and 7.6, respectively, indicating that the selectivity of nitrate ions is effectively improved.

[0132] Embodiment 10:

[0133] This example uses the anionic polyurethane prepared in Example 4, except that the other conditions are the same as those in Example 7.

[0134] The anion exchange membrane prepared in this example was applied to a small electrodialysis device under the same conditions as in Example 7. - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 3.8 and 8.2, respectively, indicating that the selectivity of nitrate ions is effectively improved.

[0135] Embodiment 11:

[0136] This example uses the anionic polyurethane prepared in Example 5, except that other conditions are the same as those in Example 7.

[0137] The anion exchange membrane prepared in this example was applied to a small electrodialysis device under the same conditions as in Example 7. - / Cl - 、NO3 - / SO4 2-The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 4.7 and 8.8, respectively, indicating that the selectivity of nitrate ions is effectively improved.

[0138] Comparative Example 3:

[0139] This example uses the anionic polyurethane prepared in Comparative Example 1, except that other conditions are the same as those in Example 7.

[0140] The anion exchange membrane prepared in this comparative example was applied to a small electrodialysis device under the same conditions as in Example 7. - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 2.0 and 6.4, respectively, indicating that the selectivity of nitrate ions is effectively improved.

[0141] Comparative Example 4:

[0142] This example uses the anionic polyurethane prepared in Comparative Example 2. Other conditions are the same as those in Example 7.

[0143] The anion exchange membrane prepared in this comparative example was applied to a small electrodialysis device under the same conditions as in Example 7. - / Cl - 、NO3 - / SO4 2- The selectivity coefficients were 0.96 and 0.95 respectively, and the modified anion exchange membrane NO3 - / Cl - 、NO3 - / SO4 2- The selectivity coefficients are 2.1 and 6.5, respectively, indicating that the selectivity of nitrate ions is effectively improved.

[0144] Table 1 Anion exchange membrane for NO3 before and after modification - / Cl - The selectivity coefficient

[0145]

[0146] It can be seen from Table 1 that the modified anion exchange membrane is better than the unmodified anion exchange membrane for NO3 - / Cl - The selectivity coefficients of the anion exchange membrane showed significant improvement, indicating that coating the hydrophobic polymer can effectively improve the selectivity of the anion exchange membrane for nitrate ions; comparing the two groups of data in Example 6 and Example 7, the results show that the modified anion exchange membrane prepared by multiple coatings of anionic polyurethane is more conducive to improving the selectivity of the modified anion exchange membrane for NO3 - / Cl - The selectivity coefficient of the modified anion exchange membrane is more effective in improving the selective separation of nitrate ions; comparing the five groups of data in Examples 7 to 11, the results show that the addition of 2-nitropropylene glycol, 1,3-dihydroxyacetone diether and DL-glycerol ether dimer in the preparation process of anionic polyurethane is beneficial to improving the selectivity of the modified anion exchange membrane for NO3 - / Cl - The selectivity coefficient of the modified anion exchange membrane can effectively improve the selectivity of the modified anion exchange membrane for separating nitrate ions. In addition, the more 2-nitropropylene glycol, 1,3-dihydroxyacetone diether and DL-glycerol ether dimer are used, the more beneficial it is to improve the selectivity of the modified anion exchange membrane for separating nitrate ions. By comparing the three groups of data of Example 7, Comparative Example 3 and Comparative Example 4, the results show that the addition of 2-nitropropylene glycol or 1,3-dihydroxyacetone diether alone in the preparation process of anionic polyurethane is not conducive to improving the selectivity of the modified anion exchange membrane for separating nitrate ions.

[0147] Table 2 Anion exchange membrane for NO3 before and after modification - / SO4 2- The selectivity coefficient

[0148]

[0149] It can be seen from Table 2 that the modified anion exchange membrane is better than the unmodified anion exchange membrane for NO3 - / SO4 2- The selectivity coefficients of the anion exchange membrane showed significant improvement, indicating that coating the hydrophobic polymer can effectively improve the selectivity of the anion exchange membrane for nitrate ions; comparing the two groups of data in Example 6 and Example 7, the results show that the modified anion exchange membrane prepared by multiple coatings of anionic polyurethane is more conducive to improving the selectivity of the modified anion exchange membrane for NO3 - / SO4 2-The selectivity coefficient of the modified anion exchange membrane is more effective in improving the selective separation of nitrate ions; comparing the five groups of data in Examples 7 to 11, the results show that the addition of 2-nitropropylene glycol, 1,3-dihydroxyacetone diether and DL-glycerol ether dimer in the preparation process of anionic polyurethane is beneficial to improving the selectivity of the modified anion exchange membrane for NO3 - / SO4 2- The selectivity coefficient of the modified anion exchange membrane can effectively improve the selectivity of the modified anion exchange membrane for separating nitrate ions. In addition, the more 2-nitropropylene glycol, 1,3-dihydroxyacetone diether and DL-glycerol ether dimer are used, the more beneficial it is to improve the selectivity of the modified anion exchange membrane for separating nitrate ions. By comparing the three groups of data of Example 7, Comparative Example 3 and Comparative Example 4, the results show that the addition of 2-nitropropylene glycol or 1,3-dihydroxyacetone diether alone in the preparation process of anionic polyurethane is not conducive to improving the selectivity of the modified anion exchange membrane for separating nitrate ions.

[0150] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

[0151] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. A method for modifying an ion membrane for selectively separating nitrate ions, comprising: The anionic adhesive is applied to the base ion membrane to form an anionic adhesive layer, and then, in a reaction solution containing a polymerized cationic monomer compound, an interfacial polymer layer is formed by interfacial polymerization, and then the preparation of the anionic adhesive layer and the interfacial polymer layer is repeated 0 to 4 times to obtain a modified anion exchange membrane; The anionic adhesive is selected from anionic polyurethane, and the anionic polyurethane has a diethylene glycol group, a 2-nitro group and a 1,3-dihydroxyacetone diether group; the polymerized cationic monomer compound is a mixture of one or two monomer substances selected from piperidine, pyrrole, dimethyldiallylammonium chloride, imidazole, chitosan and arylpiperidine aryl nitrogen heterocycle; the reaction liquid is formed by adding the polymerized cationic monomer compound to a reaction base liquid, and the reaction base liquid is a ferric chloride solution, and the concentration of ferric chloride in the reaction base liquid is 0.1-1 mol / L; the base ion membrane is an anion exchange membrane; the anion adhesive layer and the interface polymer layer form a hydrophobic polymer coating, and the number of layers of the hydrophobic polymer coating in the modified anion exchange membrane is 1-5 layers; the preparation of the anionic polyurethane includes: S1: mixing phthalic anhydride polyester polyol, diethylene glycol, toluene diisocyanate and a hydroxy compound to generate an intermediate 1; the hydroxy compound is at least one of 2-nitroglycerin and 1,3-dihydroxyacetone diether; S2: Continue to raise the temperature of intermediate 1, keep the temperature to react, add acetone, and obtain intermediate 2; S3: The pH of the intermediate 2 is adjusted, and then deionized water is added for emulsification, and the acetone is removed in vacuo to obtain the anionic polyurethane.

2. The method for modifying an ion membrane for selectively separating nitrate ions according to claim 1, characterized in that: The anionic binding layer is activated by NaOH solution.

3. The method for modifying an ion membrane for selectively separating nitrate ions according to claim 1, characterized in that: The anion exchange membrane is selected from a homogeneous anion exchange membrane, a semi-homogeneous anion exchange membrane or a heterogeneous anion exchange membrane.

4. The method for modifying an ion membrane for selectively separating nitrate ions according to claim 1, characterized in that: The mass ratio of the base ion membrane to the anionic adhesive is 95:5-25.

5. The modified anion exchange membrane prepared by the ion membrane modification method for selectively separating nitrate ions according to any one of claims 1 to 4.

6. Use of the modified anion exchange membrane according to claim 5 in wastewater treatment.

Citation Information

Patent Citations

  • Preparation method of anion exchange membrane with monovalent selective separation function

    CN104815568A

  • Crown ether modified cation exchange membranes for selective recovery of ionic species and methods of making and using the same

    US20240252991A1